Usefulness of examination of some tumor markers in the diagnostics of pancreas cancer - Mroczko, Barbara; Snarska, Jadwiga; Chlabicz, Marcin; Dariusz Szajda, Sławomir; Skrzydlewski, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2004)
Diagnostics of pancreas cancer is mainly based on applying imaging methods, USG and computer tomography. Additional examination involves the determination of tumor markers, which allow pancreas cancer to be detected and its treatment to be controlled. Antigen accompanying digestive tract cancers is the basic and well known marker in the diagnostics of pancreas cancer (CA 19-9). Cathepsin D and cancer procoagulant are relatively vaguely known markers in oncological diagnostics of pancreas cancer. The study aimed at evaluating usefulness of Ca 19-9, cathepsin D and CP in pancreas cancer detection. The examination material included blood serum of 11 pancreas cancer patients and 11 controls. CA 19-9 concentration was determined using the immunoenzymatic method (MEIA) using Axym analyzer manufactured by Abbott and expressed in IU/ml. Cathepsin D activity was examined using Folin-Ciocalteau method in copper modification and was expressed by the quantity of released tyrosine in nM Tyr/ml/4 hours. CP activity was examined using the coagulation method of Gordon and Benson, expressing it by coagulation period in second (s). CA 19-9 concentration was found to be more than 19 times higher as compared to the high referential value for CA 19-9 in the blood serum (on the basis of the obtained results). CP activity in pancreas cancer patients is more than 3 times higher than mean activity of this enzyme in the blood serum of healthy controls. Differences between the examined and the control material are statistically significant (p<0.001) both for CA 19-9 and CP. Cathepsin D activity in blood serum of pancreas cancer patients is close to the normal values. The obtained results confirm the high diagnostic value of examination of CA 19-9 concentration and suggest also the possibility of applying the examination of CP activity in oncological diagnostics of the pancreas.